Partially reversible lung consolidation after revascularization of a total occlusion of both left pulmonary veins following ablation of atrial fibrillation: a case report. Issue 2 (2nd February 2023) - Ahero, Anete; Frauenfelder, Thomas; Breitenstein, Alexander; Ammann, Peter; Kucher, Nils; Barco, Stefano
Abstract: Background: The use of pulmonary vein (PV) radiofrequency ablation for atrial fibrillation (AF) treatment may be complicated by PV stenosis or occlusion. A common curative treatment for symptomatic patients is a transcatheter intervention, including percutaneous transluminal balloon angioplasty and stent implantation. Stent implantation itself, however, can be complicated by in-stent stenosis. Case summary: A 26-year-old man presented with worsening exertional dyspnoea due to a total occlusion of both left PVs after the isolation of two PVs for AF. Chest computed tomography (CT) showed chest asymmetry and consolidation of the left lung. The patient was treated with balloon angioplasty and stent placement of both left PVs, resulting in improvement of symptoms, walking distance, and increase in lung space volume by 120 mL based on CT-based volumetry. Ten months later, the patient experienced a recurrence of similar symptoms. A high grade in stent restenosis of the upper left PV and moderate in stent restenosis of the lower PV were diagnosed and treated with angioplasty. The patient was discharged from the hospital in good clinical condition 3 days after the intervention. Discussion: Non-specific symptoms of PV stenosis or occlusion, such as shortness of breath, fatigue, flu-like symptoms, reduced physical performance, and haemoptysis delay the diagnosis. If unusual symptoms appear abruptly after PV isolation, a PV stenosis should be considered. In this case, we describe for the first time a partially reversible consolidation of lung parenchyma following the revascularization of both PVs.